ETIKA KOMUNIKASI NABI MUHAMMAD (KAJIAN DESKRIPTIF-ANILITIK PADA HADITS NO. 59 DALAM SHAHIH BUKHARI, KITAB ILMU) - Deli Luthfi Rahman (ADISAM PUBLISHER, 2025)
The success of Prophet Muhammad as a leader was not only supported by military strength but also by his ability to communicate effectively while upholding ethical communication principles such as politeness, clarity, and consideration of his audience’s background. He conveyed his message with divine guidance through various wise methods and approaches, as reflected in the hadith narrated by his companions. This study aims to examine the communication ethics of Prophet Muhammad in Hadith No. 59, as recorded by Imam Bukhari in Sahih Bukhari, Kitab al-‘Ilm (Book of Knowledge). The research employs a descriptive-analytical method to analyze the ethical communication elements and principles applied by Prophet Muhammad in his interactions with his companions, as depicted in the hadith text. The study identifies three key communication ethics principles demonstrated by the Prophet: cortessiveness (politeness), mutual understanding, and evaluative prejudice (judgment or evaluation). First, cortessiveness refers to politeness in communication, which includes not interrupting a speaker, prioritizing the right of the first speaker, and not ignoring questions. Second, mutual understanding ensures a shared comprehension between communication actors; the Prophet understood the Bedouin Arab, and vice versa. Third, evaluative prejudice pertains to forming judgments and assessments cautiously to prevent misunderstandings that could disrupt communication. Thus, cortessiveness, mutual understanding, and evaluative prejudice serve as fundamental ethical principles in prophetic communication